Tingkat Kepuasan Pasien Rawat Inap Pada Pelayanan Makanan di Rumah Sakit Tk IV 04.07.01 Tegal - Rahmawati, Yuniarti Dewi; Eliyanti; Wahyani, Anggray Duvita (Universitas Muhadi Setiabudi, 2025)
ABSTRACT Hospital kitchen Tk.IV 04.07.01 Tegal is part of a nutrition installation that functions as a services operations process, it is necessary to improve food services for inpatients at Tk.IV Hospital 04.07.01 Tegal through customer satisfaction. Objective in this riset is To determine patient satisfaction with nutrition services at Tk.IV Hospital 04.07.01 Tegal. Researchers used a survey method on patients aged 25-45 years. In Tangibles patient satisfaction (real form) obtained 66.6%, in the aspect of Reliability (reliability) obtained 65%, the aspect of Responsiveness expectation (agreness) obtained a score of 63%, in the aspect of Assurance (assurance) obtained a score of 80% and on the aspect of Empathy (empathy) obtained a percentage of 78%. all aspects of expectations have a smaller score than the reality score so it can be said that the food service has met expectations because reality is greater than expectations. Patient satisfaction with food service at Tk.IV Hospital 04.07.01 Tegal at the Satisfied level with the aspect that has a big influence on customer satisfaction, namely Assurance (guarantee)